Cost-effectiveness of testing for CYP2C19 loss-of-function carriers following transient ischemic attack/minor stroke: A Canadian perspective. Issue 4 (April 2023) - Micieli, Andrew; Singh, Nishita; Jahn, Beate; Siebert, Uwe; Menon, Bijoy K; Demchuk, Andrew M
Background: The CHANCE-2 study compared 3 weeks of aspirin–ticagrelor to aspirin–clopidogrel in CYP2C19 loss-of-function (LOF) allele carriers following a transient ischemic attack (TIA)/minor stroke and demonstrated a modestly lower risk of stroke recurrence with aspirin–ticagrelor. This stroke protection was largely for minor stroke and came at an increased risk of bleeding. The cost-effectiveness of implementing testing for LOF allele status to personalize antiplatelet regimen for secondary stroke prevention after a TIA/minor stroke in the Canadian health care context is unknown. Methods: Cost-effectiveness analysis using a decision-analytic Markov cohort model with a lifetime horizon was performed to determine the costs and health benefits of testing for LOF allele status compared with no testing (current standard of care). The population of interest was patients living in Canada who suffered a TIA/minor stroke. Outcomes of interest were life-years gained (LYG), quality-adjusted life years (QALY) gained, costs (reported in 2022 Canadian dollars), and the incremental cost-effectiveness ratio (ICER). We adopted the perspective of the Federal, Provincial, and Territorial Ministries of Health and used a 1.5% annual discount rate. Sensitivity analyses were performed to assess uncertainty. Results: Compared to standard of care, LOF allele testing leads to 0.14 LYG (undiscounted), 0.12 QALYs gained (undiscounted), and additional lifetime costs of CAD432 (discounted) per patient. The ICER of the LOF allele testing strategy is CAD4310 per QALY gained compared with standard of care. The probabilistic sensitivity analyses demonstrated that LOF allele testing was cost-effective in more than 99.99% of simulations using a willingness-to-pay threshold of CAD50, 000 per QALY. Conclusion: Based on available evidence, testing for LOF allele followed by short duration 3 weeks of aspirin–ticagrelor compared to standard-of-care aspirin–clopidogrel can lead to prolonged life and improved quality of life and can be considered very cost-effective when compared with other well-accepted technologies in health and medicine.